Healthy habits as possible sleep difficulty protectors in a Mexican national university’s medical students - Tafoya, Silvia (2013)
Medical students have a high percentage of poor sleepers; more evidence on how health habits contribute to sleep better in this population is needed. Objectives: To identify the association of some health habits with presence/absence of sleep difficulties in medical freshmen. Design: Cross-sectional, descriptive study. Setting: Faculty of Medicine, Universidad Nacional Autonoma de Mexico. Participants: Medical students. Interventions: The presence/absence of sleep difficulties was assessed by three items from the Symptom Check List (SCL 90) in 572 medical students 18.6 year-old (SD±2.7) average, 37% men and 63% women. Sleep-related habits were determined by 18 items from the Nowack Stress Profile. Main outcome measures: Sleep habits. Results: Simple analyses showed that absence of sleep difficulties was associated with the "high promotion of rest sleep" (OR=0.15; CI95%=0.04-0.64) and "high risk prevention" (OR=0.59; CI95%=0.41-0.86). Conclusions: The "promotion of rest-sleep" was the least reported habit by students, but explained absence of sleep difficulties better than other health habits.